Transformasi “Nongkrong” di Era Digital: Studi Kasus di Warkop Bandar Kupi Kota Medan - Prabhaswara, Muhammad Prakoso; Gustan, Gustan; Ginting, Rahmanita (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study aims to understand how the digital era has transformed the way people "Ngongkrong" at Warkop Bandar Kupi Kota Medan. In today's digital landscape, coffee shops, which were once social hubs for gathering and socializing, have evolved into more individualistic spaces where the use of gadgets and internet access dominates interactions. This research employs a survey method involving 50 respondents to analyze their visiting frequency, gadget usage, and communication preferences. The findings reveal that most visitors use their gadgets intensively while at the coffee shop, with 50% of respondents preferring digital activities over direct social interaction. However, face-to-face communication remains significant for 60% of respondents. Wi-Fi has become the main attraction for 70% of visitors, although 55% believe that gadget usage has reduced the essence of togetherness. In conclusion, while digital technology provides convenience and easy access to information, it also poses challenges to social interactions in coffee shops. To maintain a balance, coffee shop management can implement strategies such as organizing offline events or creating gadget-free zones to enhance meaningful social interactions.